2023
DOI: 10.3390/robotics12050131
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Parallel Robots: Rehabilitation, Assistance, and Humanoid Applications for Neck, Shoulder, Wrist, Hip, and Ankle Joints

Victoria E. Abarca,
Dante A. Elias

Abstract: This review article presents an in-depth examination of research and development in the fields of rehabilitation, assistive technologies, and humanoid robots. It focuses on parallel robots designed for human body joints with three degrees of freedom, specifically the neck, shoulder, wrist, hip, and ankle. A systematic search was conducted across multiple databases, including Scopus, Web of Science, PubMed, IEEE Xplore, ScienceDirect, the Directory of Open Access Journals, and the ASME Journal. This systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…However, dynamic interactions with highly variable and poorly characterized objects (i.e., patients with neurological impairments) do not destabilize the impedance controller. This is essential for safe operation in a clinical setting [22].…”
Section: Wrist Robot Device Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dynamic interactions with highly variable and poorly characterized objects (i.e., patients with neurological impairments) do not destabilize the impedance controller. This is essential for safe operation in a clinical setting [22].…”
Section: Wrist Robot Device Control Systemmentioning
confidence: 99%
“…It should be noted that the review articles found in the literature do not have the wrist as their main focus, covering other joints of the upper and lower limbs [3,4,[19][20][21][22] or are not up-to-date [1]. The review articles [1,3,4,[19][20][21][22] also do not clearly present how to conduct the mathematical modeling of the new device based on the characteristics of the human wrist as detailed in this paper.…”
Section: Introductionmentioning
confidence: 96%
“…Then, in 2023, Abraca et al [5] presented a systematic review on parallel robots used in the fields of assistive technologies, humanoids, and rehabilitation robots. Robots for rehabilitation are applied to help people who have been injured or ill to regain their strength, functionality, and motor skills.…”
Section: Related Workmentioning
confidence: 99%
“…The medical field has greatly benefited from the use of parallel robots, which have found use in humanoids, assistance, and rehabilitation. Future prospects show that parallel robots may become a market mainstay due to ongoing technical advancements and cooperation between the scientific community, business, and healthcare experts [5].…”
Section: Introductionmentioning
confidence: 99%